Cost modelling techniques for availability type service support contracts: a literature review and empirical study - Datta, Partha Priya (Cranfield University Press, 2009)
The research in this paper is focused on enhancing existing knowledge in cost estimation models at the bidding stage of service support contracts. The difficulty of this task lies in the long lasting contracts, which in some cases may reach even 40 years. The paper first reports the existing knowledge through detailed review of literature. The paper studies different service support contracts and reports the cost modelling techniques used in availability type contracts in the context of defence and aerospace industry. The contribution of this paper is to identify the key areas of improvement and business priorities in the area of cost modelling of availability type service support contracts.
Organised by: Cranfield University
Keywords: Cost Modelling; Availability Type Service Contracts; Literature Review